Uterine Rupture in Pregnancy following Two Abdominal Myomectomies and IVF - Marco D’Asta; Ferdinando Antonio Gulino; Carla Ettore; Valentina Dilisi; Elisa Pappalardo; Giuseppe Ettore (Case Reports in Obstetrics and Gynecology)
Objective. Uterine rupture (UR) during pregnancy is an obstetric emergency that could determine poor maternal and neonatal outcomes. There are many factors that could increase the risk of UR, such as a previous myomectomy. The aim of this study is to evaluate the role of a previous myomectomy in a spontaneous UR in pregnancy. Methods. A 33-year-old primigravida comes to our obstetric emergency room for pelvic pain at 29 weeks of gestation. In her medical history, there were two previous surgical operations of abdominal myomectomy, one in 2015 and one in January 2021 (6 months before conception). After 34 minutes, a pubo-subumbilical longitudinal laparotomy was performed for pathological decelerations in the cardiotocography. In the peritoneal cavity, there was 500 mL of blood serum liquid. The right arm and shoulder of the fetus were extending out of the uterus across a breach of 5 cm near the right tubal corner. A corporal incision was performed, and a healthy baby was born and moved to neonatal intensive unit care. Results. A UR can occur at any stage of pregnancy, mostly during the third trimester of pregnancy. Risk factors that increase the incidence of a uterine rupture after myomectomy include a short period (i.e., <12 months) between the myomectomy and conception, the opening of the endometrial cavity, and large myomas (with a maximum diameter above 4 cm). Uterine rupture during pregnancy after abdominal myomectomy seems to be less frequent than after a laparoscopic one. Conclusion. Uterine rupture is an obstetric emergency; it is mandatory to consider this eventuality in pregnancy, particularly in the third trimester, if there was a previous laparoscopic myomectomy in the anamnesis of the patient.